An innovative state-of-the-art health storytelling technique for better management of type 2 diabetes - Sumbal Ali; Shumaila Bakht; Atta Ullah Jan; Iftikhar Alam; Ali Madi Almajwal; Tareq Osaili; Tareq Osaili; Tareq Osaili; Reyad Shakir Obaid; Reyad Shakir Obaid; MoezAllslam Ezzat Faris; MoezAllslam Ezzat Faris; et al. (Frontiers Media S.A., 2023)
BackgroundType 2 diabetes (T2D) is a chronic lifelong disease that requires long-term prevention and management strategies in a community setting. A health story is a novel technique that may be used as an effective tool for better prevention and management of T2D.ObjectiveThe main objective of this study is to develop a story to be used as a social health technique based on contemporary scientific knowledge that may be used at a community level for better communication and management of T2D.MethodsA community-academic partnership was formed with a not-for-profit Nutrition Education, Awareness, and Training (NEAT) organization in Khyber Pakhtunkhwa, Pakistan. We agreed to develop a story that may be used as a health and nutrition education communication tool for better management of patients with T2D. The following phases were followed during the story creation process: (1) the theory phase, (2) the modeling phase, and (3) the evaluation phase. Raters evaluated the story to determine its literary and scientific quality, comprehensiveness, and T2D specificity.ResultsThe title of the story translated into English is "The Story of Diabetes-The Story of Success." It is text based and contains 86 pages in the local language, "Pashto," with an English translation. The story is divided into five chapters and describes the initial diagnosis, fear associated with the disease, issues related to referral to certified practitioners, the importance of a balanced diet, and related lifestyle habits. After story evaluation, the raters suggested its literary and scientific quality, comprehensiveness, and T2D specificity (Pearson correlation scores of >0.8).ConclusionThis unique story was created for T2D and found to be of significant quality in terms of its literary and scientific quality, as well as its comprehensiveness and diabetes specificity. As a result, it may be suggested that it can be used in subsequent studies to improve T2D management among adult patients.